Analisis Kesalahan Peserta Didik dalam Menyelesaikan Soal Literasi dan Numerasi Berdasarkan Tahapan Kastolan - khairunisa, Nuke Ferli Khairunisa; Subhan Ajiz Awalludin; Awalludin, Subhan Ajiz (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to analyze students' errors in solving literacy and numeracy problems based on Kastolan's stages and to identify the factors that contribute to these errors in order to minimize them during the learning process. This research employs a qualitative method with a study case. The subjects selected were six students out of a total of 36 students in class X-2 at SMAN 94 Jakarta. The results of the study indicate that the level of students’ literacy and numeracy skills influences the types and frequency of errors made. The conclusion reveals the factors behind each type of error: (1) conceptual errors occur due to a lack of understanding of the material and basic concepts, which leads students to choose incorrect formulas; (2) procedural errors arise from students’ inability to organize the steps of problem-solving in a sequential and systematic manner; and (3) technical errors result from inaccuracy in modeling the problem into mathematical form, such as writing incorrect variables or numbers.   Keywords: Erros Analysis, Kastolan Stages, Literacy and Numeracy Issues